γ-Aminobutyric acid (GABA) content in different varieties of brown rice during germination - D. Karladee (2018)
Rice grains rich in gamma-aminobutyric acid (GABA) are increasing in popularity, particularly in the health food market. GABA levels in rice are influenced by many factors, including the duration of incubation of seeds, particularly in pre-germinated brown rice grains. In this report, five different incubation durations (0, 12, 24, 36, and 48 h) and 21 rice varieties (11 landraces purple rice and 10 modern white varieties) were tested. Results show that GABA content increased steadily from 3.96 mg/100 g dry matter at 0 h duration (i.e., no incubation period) to 10.04 mg/100 g dry matter after 12 h, reaching the highest levels of 17.87 mg/100 g dry matter at 24 h incubation, and then decreased continuously afterwards to 9.91 and 1.36 mg/100 g dry matter at 36 and 48 h, respectively. A correlation of GABA levels at 0 h and 24 h was detected (r = 0.48). Genotypic variation was detected from a minimum of 6.50 to a maximum of 10.10 mg/100 g dry matter, with a mean of 8.03. At 24 h, the white rice variety KDML 105 and the purple rice variety Kum Doi Saket (23.48 and 23.63 mg/100 g dry matter, respectively) exhibited the highest GABA content of all 21 rice varieties. This indicates the importance of the local purple rice cultivars for adding nutritional value to functional food products.